Child public health indicators for fragile, conflict-affected, and vulnerable settings: A scoping review. - Ayesha Kadir; Amy J Stevens; Emi A Takahashi; Sham Lal (PLOS Global Public Health)
Children and young people are disproportionately vulnerable to harm during crises, yet child public health expertise is limited in humanitarian settings and outcomes and impact data are lacking. This review characterises child public health indicators that are routinely collected, required by donors, and recommended for use in fragile, conflict-affected, and vulnerable (FCV) settings. We conducted database and grey literature searches and collected indicators from technical agencies, partnerships, donors, and nongovernmental organisations providing child public health services in FCV settings. Indicators were included if they were child-specific or disaggregated for ≤18 years. Indicators were coded into domains of health status, health service, social determinants, and health behaviours and analysed for trends in thematic focus and clarity. A total of 668 indicators were included. Routinely collected indicators (N = 152) focused on health status and health services. Donors required only 14 indicators. Technical bodies and academics recommended 502 indicators for routine measurement. Prioritised topics included nutrition, paediatrics, infectious diseases, mortality, and maternal-newborn care. There were notable gaps in indicators for child development and disability. Child protection indicators were not routinely collected, despite being the focus of 39% of recommended indicators. There were overlaps and duplications, varied age disaggregations, and 49% of indicators required interpretation to measure. The review demonstrates that it is feasible to routinely measure child public health outcomes in FCV settings. Recommendations from technical agencies and partnerships are characterised by numerous indicators with duplication, poor definitions, and siloed sector-specific focus. There are gaps in measurement of critical child public health topics. To improve safety and effectiveness of interventions for child public health, consensus is needed on priority topics and a shortlist of quality, standardised indicators that governmental and nongovernmental actors can be reasonably expected to measure. Indicators should be prioritised to support decision-making and include proxy indicators for periods when routine measurement is hampered.